Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.